CT-Guided Occipital Condyle Biopsy: A Case Report and Review of the Literature - Morcet Delattre, Thibaud; Voisin, Steven; Rabeau, Valentin; Rolland, Yan (Journal of Clinical Interventional Radiology ISVIR, 2025)
Metastasis of breast cancer to the occipital condyle presents challenges in histopathologic diagnosis and treatment due to its difficult localization. A few surgical and radiological approaches have been described, with various level of complexity.The case presentation describes a 43-year-old woman with persistent occipital neuralgia, diagnosed with a lytic mass on the left occipital condyle via head magnetic resonance imaging. A computed tomography-guided biopsy confirmed breast carcinoma metastasis without any complication, highlighting the efficacy and safety of the posterior ascending occipital condyle approach for bone biopsies.
Keywords: image-guided biopsy; occipital bone; breast cancer